Plastik Biodegradable dari Pati Buah Sukun Dengan Penambahan Plasticizer Gliserol - Indah Nulfia; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2022)
Efforts were made to improve the quality of the use of breadfruit by processing it into a variety of products, increasing the economic value and better shelf life. The concentration of glycerol used was 0.4 ml; 0.8 ml; 1.2 ml; 1.6 ml; 2ml. The results of this study showed the greatest strength value was the addition of 0.4 mL glycerol with a tensile strength value of 21.72 Mpa and the elongation value at 0.4 mL glycerol 9.37%, the elasticity was 373.27 Mpa. Meanwhile, the water content and swelling test increased with the addition of glycerol plasticizer at the addition of 2 mL. biodegradation test on day 12 biodegradable plastic can be completely decomposed. In the FTIR test, no new functional groups were found.